Optimization of Natural Dye Extraction from Avocado Skin (Percea Americana Mill) Using the Taguchi Method - Amborowati, Cindi; Hidayat, Arif; Retno Sawitri, Dyah (Jurnal Ilmiah Teknik Kimia, 2025)
Natural dyes were created to replace the use of artificial dyes. One plant that can be used as a natural dye is avocado skin (Percea Americana Mill). Avocado skin can be extracted using Ultrasonic Assisted Extraction (UAE) to obtain tannins as color pigments. The aim of this research is to optimize process conditions and evaluate the influence of the interaction of factors that influence the extraction process of natural dyes from avocado skin using the Taguchi method. The research method begins with cleaning, drying and reducing the size of the avocado skin as desired. Then the avocado skin is extracted using the UAE method with varying ultrasonic power, extraction time, and the ratio of ingredients and solvents. Then it is evaporated using a rotary evaporator to evaporate the remaining solvent. The resulting extract was then analyzed for total tannins to optimize the extraction process using the Taguchi method. From the experimental results, the optimum yield was obtained at an ultrasonic power of 75%, a material and solvent ratio of 1:04, and an extraction time of 60 minutes. The optimum tannin concentration was obtained at a material and solvent ratio of 1:12, extraction time of 35 minutes, and ultrasonic power of 25%.